Analisis Situation Awareness Pada Aktivitas Kerja Petugas Aviation Security Di Bandar Udara Internasional Zainuddin Abdul Majid Lombok - Sultan Kurnia Alamsyah; Djoko Widagdo (Jurnal Ilmiah Dan Karya Mahasiswa, 2023)
Situation Awareness (SA) is a person's perception or response to be able to understand conditions or circumstances in the surrounding environment. Aviation Security officers' situation awareness is very important because it can influence the officers' performance and success in carrying out their duties and responsibilities in the field. This research aims to determine the process of implementing Situation Awareness in the work activities of Aviation Security officers at Zainuddin Abdul Majid Lombok International Airport and efforts to increase Situation Awareness.  This research uses a descriptive qualitative approach, namely the data used is primary and secondary data. Primary data is observation and interview data, while secondary data is references to previous research.The results of this research show that the process of implementing Situation Awareness for Avsec officers has identified 3 SA indicators at level I, then 4 indicators for SA level II and 2 indicators for SA level III in the work activities of Avsec officers. The level of situational awareness that Avsec officers have on a scale of levels 1-3 is already at level 3, because officers can understand work situations well and can solve problems effectively in their environment, so that Avsec officers' situational awareness is already at level 3. Efforts to improve situation awareness, namely officers are able to understand and analyze every condition in the field by referring to SOPs, briefings before work, always coordinating well when working, every year holding a refreshing course to increase awareness and maintain ability to work. Avsec officers are able to resolve problems well and professionally.